Dripping with Blood and Dirt from Head to Toe: Marx's Genealogy of Capitalism in Capital, Volume 1. (13th September 2022) - Allen, Amy
Abstract: I argue that Marx's critique of political economy in volume 1 of Capital relies on a kind of genealogical argument that takes capitalism as its object. In the first section of the article, I sketch out an interpretation of the argumentative structure of Capital 1, highlighting what I take to be the two crucial turning points in Marx's critique of political economy. Marx's specifically genealogical argument comes to the foreground with the second of these turning points, which can be found at the start of his account of primitive accumulation in Part 8 of Capital 1. The first part of the paper defends the thought that the genealogy of capitalism's prehistory is no mere digression from or complement to the main theoretical argument, but rather the crucial completion of Marx's critique of political economy in Capital 1. In the second part of the paper, I turn to the somewhat thornier question of what sort of genealogy Marx offers. Drawing on and extending Bernard Williams's distinction between vindicatory and subversive genealogies, I contend that Marx's genealogy of capitalism, despite containing both subversive and vindicatory strands, is embedded in a longer vindicatory historical arc that, while avoiding crude teleologies and strong claims to unilinearity, nonetheless maintains a kind of necessity claim for its genealogical object.